Indonesian Dental Students' Attitudes, Knowledge, Preparation, and Willingness to Treat HIV/AIDS Patients - Wimardhani, Yuniardini Septorini; Ossa, Yuli Fatzia; Wardhany, Indriasti Indah; Maharani, Diah Ayu; Lee, Cliff (European Journal of Dentistry, 2022)
Objective To assess the Indonesian dental students' knowledge of HIV/AIDS in terms of transmission and oral manifestation, the attitudes toward people living with HIV/AIDS (PLWHA), the preparedness in infection control, and willingness to treat PLWHA, and assess the factors for willingness to treat PLWHA.Materials and Methods A modified version of a questionnaire used to assess dental students' knowledge, attitude, preparedness, and willingness to treat PLWHA in China was used. The questionnaire was cross-culturally adapted into Indonesian and had been pre-tested for face validity and test and retest reliability. The dental students from 32 dental schools in Indonesia were invited to participate in the study.Results A total of 1,280 dental students from 23 dental schools participated in the study. This study found that only 63% of students scored higher than 70% for knowledge of HIV/AIDS, and the mean score for knowledge was 15.02 (2.4). Higher than 80% of students had a positive professional attitude toward PWLHA; however, 80% of students worried about possible disease transmission in the dental office by PLWHA and 70% of students overestimated the occupational risk when treating PLWHA. The dental students had good preparedness for infection control with a mean score for preparedness of 3.19 (0.4). The mean score for willingness was 2.5 (0.9). Willingness to treat significantly differed by the type of universities, gender, age, and clinical experience. This study showed that knowledge about HIV/AIDS correlated with the willingness to treat PLWHA among dental students.Conclusion Dental students who have good knowledge about HIV infection tend to have a good willingness to treat PLWHA. The knowledge would in turn affect their attitude, preparedness, and willingness to provide care for PLWHA with confidence and comfort. This study suggests that the improvement of dental training may play an important role in changing students' perception of willingness to treat PLWHA.
Keywords: HIV; dental care; attitude; willingness to treat; dental education; Indonesia